Them and Us – Pintér Béla’s Blood-Red, Off-White, Dark Green and András Urbán’s Sacra Hungarica in Context - Schandl, Veronika (Analyses/Rereadings/Theories: A Journal Devoted to Literature, Film and Theatre, 2023)
The paper wishes to document a recent trend visible in the Hungarian independent theatre scene – a turn towards social, political issues, as well as a growing sensitivity towards the visible tensions in Hungarian political discourse. It does so through the analysis and the contextualization of two recent Hungarian independent theatrical productions. Studio K’s 2019 Sacra Hungarica is an in-your-face attempt to portray the current distortion of the language and the abuse language is used for, while Béla Pintér’s Blood Red, Off-White, Dark Green, a clever Oedipus Rex paraphrase that depicts marginalization, racism, and nationalism in a pointedly non-pc allegory. The essay introduces the status of independent theatre vis-à-vis politics after 1989 and will delineate the changes the conservative governments brought into the alternative scene. Then, through an in-depth analysis of the above-mentioned two productions, it discusses the various means of theatricality they use to comment on contemporary Hungary.